KINERJA SUHU PADA RUMAH TINGGAL KONSTRUKSI DINDING BAMBU PLESTER - Aulia Fikriarini Muchlis (lp2m-uin malang, 2010)
Every single design of architecture have to present a convenience by considering the local climate, means there must be balance between climate and architecture in order to get the expected convenience. Wall as a skin of the building is relatively strike by the effects of hot, damp, and wind has to give thermal convenience and does not increase global warming either its materials or its construction. “Bamboo” which is made of cement is an efficient and best alternative for building wall. Then, this research is aimed to count the convenience of temperature inside the room of certain building which takes the bamboo as its wall.This is a quantitative research that uses comparison strategy. It is the comparison between the construction of vertical bamboo wall and woven bamboo wall. The air temperature inside the room (Ti) is the main factor that is measured by using hygro termometer. The results show that the construction of woven bamboo wall has better value of convenience of temperature than vertical one. I hope that this research give the valuable contribution about the benefits of bamboo.